Closing the gender gap in climate-smart agriculture - Vermeulen, Sonja J. (2015)
Climate-smart agriculture (CSA) has become a central concept shaping action and bringing together constituencies at the global level on agriculture and climate change. In essence, climate-smart agriculture pays explicit attention to how interventions in agriculture and food systems affect each of three key outcomes: food security, adaptation and mitigation (FAO 2013). The climate-smart agriculture movement is not prescriptive about how best to achieve these outcomes, nor how to manage the inevitable trade-offs – the idea is that locally appropriate priorities and solutions will be generated. A key question arises as to the winners and losers from these processes, in terms of gender as well as other social dimensions, and whether climate-smart agriculture help transform agriculture and rural development in ways that achieve major gains for gender equity.